Efficacy of antibiotic therapy in urogenous reactive arthritis and peripheral variant of ankylosing spondyloarthritis - M M Urumova; E R Agababova; S. I. Soldatova; S V Shubin (Научно-практическая ревматология)
Objective. To study efficacy of antibiotics from two different groups - asitromycin/sumamed (macrolid) and lomefloxacine/maxaquine (ftorquinolone) in urogenous rheactive arthritis (URA) and peripheral variant of ankylosing spondyloarthritis (PVAS) with signs of urogenital Chlamidia inflammation. Material and methods. 86 pts were examined: 51 with URA (including Reiter’s disease - RD) and 35 with PVAS. Diagnoses of URA, RD and PVAS were definite in all pts. 43 pts received sumamed in total dose of I5g, 43 - maxaquinum - 24g total. Treatment efficacy was assessed according to clinical and laboratory indices changes immediately after the end of treatment and then in 1 and 3 months. Results. Similar significant decrease of swollen and tender joint counf as well as laboratory activity indices accompanied by disappearance of urogenital inflammation signs was seen in URA and PVAS. Conclusion. Antibiotics administration for chlamidiosis is indicated in all cases of URA and PVAS with urogenital inflammation signs.